Mothers´ Attitude Towards Orodental Health of Their 1-6 Years Old Children Referred To Medical Centers of Zahedan City, 2006 - M.Naderifar; H.Peyrovi; F.Galgay (Iran University of Medical Sciences, 2007)
Background & Aim: Healthy community is strictly dependent on having healthy children, whose orodental hygiene is a necessity for maintaining health. Orodental care must begin from childhood, because performing special care of milk teeth of children would guarantee optimal growth of permanent teeth. Family, as an agent fostering physical and psychosocial aspects of the child can help to population health in parallel sith health care systems through educational and health activities. This paper aim at investigating mothers´ attitude of orodental health of their 1-6 years children referred to health treatment centers. This study was designed to determine the mothers´ attitude of mothers´ of orodental health of their 1-6 years old children.  Material & Method: This was a cross-sectional study in which data was gathered using questionnaire and interview. Five hundreds mothers of 1-6 years old children, selected by random sampling method, took part in the study. Results: According to findings, the percentage of mothers with positive, inert, and negative attitude were respectively 79.6%, 20.4%, and 0%. There was direct positive relationship between attitude and mothers' age and education, age of children and economic status.00). Conclusion: It is of great importance that authorities plan systematic and strict educational programs using mass media, and any other facility suitable for the purpose to make mothers knowledgeable about the subject. It is suggested to study the causes of inappropriate practice among mother in future studies.